Effects of ketone body 3-hydroxybutyrate on cardiac and mitochondrial function during donation after circulatory death heart transplantation - Jacob Marthinsen Seefeldt; Yaara Libai; Katrine Berg; Nichlas Riise Jespersen; Thomas Ravn Lassen; Frederik Flyvholm Dalsgaard; Pia Ryhammer; Michael Pedersen; Lars Bo Ilkjaer; Michiel A. Hu; Michiel E. Erasmus; Roni R. Nielsen; et al. (Scientific Reports, 2024)
Abstract Normothermic regional perfusion (NRP) allows assessment of therapeutic interventions prior to donation after circulatory death transplantation. Sodium-3-hydroxybutyrate (3-OHB) increases cardiac output in heart failure patients and diminishes ischemia–reperfusion injury, presumably by improving mitochondrial metabolism. We investigated effects of 3-OHB on cardiac and mitochondrial function in transplanted hearts and in cardiac organoids. Donor pigs (n = 14) underwent circulatory death followed by NRP. Following static cold storage, hearts were transplanted into recipient pigs. 3-OHB or Ringer’s acetate infusions were initiated during NRP and after transplantation. We evaluated hemodynamics and mitochondrial function. 3-OHB mediated effects on contractility, relaxation, calcium, and conduction were tested in cardiac organoids from human pluripotent stem cells. Following NRP, 3-OHB increased cardiac output (P < 0.0001) by increasing stroke volume (P = 0.006), dP/dt (P = 0.02) and reducing arterial elastance (P = 0.02). Following transplantation, infusion of 3-OHB maintained mitochondrial respiration (P = 0.009) but caused inotropy-resistant vasoplegia that prevented weaning. In cardiac organoids, 3-OHB increased contraction amplitude (P = 0.002) and shortened contraction duration (P = 0.013) without affecting calcium handling or conduction velocity. 3-OHB had beneficial cardiac effects and may have a potential to secure cardiac function during heart transplantation. Further studies are needed to optimize administration practice in donors and recipients and to validate the effect on mitochondrial function.